A real-world, cross-sectional, community survey of symptoms and health-related quality of life of adults with acute myeloid leukemia. (26th March 2019) - Mamolo, Carla M; Cappelleri, Joseph C; Hoang, Caroline J; Kim, Ruth; Hadfield, Anna; Middleton, Chloe; Rider, Alex; Walter, Roland B
Aim: We used Adelphi Real World Disease-Specific Programme data to characterize adults with newly diagnosed or relapsed/refractory de novo acute myeloid leukemia (AML).Materials & methods: Community-practice hematologists/oncologists completed patient record forms for their regular AML patients. Patients were invited to complete patient self-completion forms including 3-Level EuroQol 5-Dimensions (EQ-5D-3L) and Functional Assessment of Cancer Therapy–Leukemia (FACT-Leu) questionnaires.Results: Physicians provided patient record forms for 389 patients (339 newly diagnosed, 50 relapsed/refractory); 68 patients completed patient self-completion forms. Mean EQ-5D visual–analog scale and index and FACT-General scores were significantly lower than US population norms (p < 0.0001); health-related quality of life (HRQoL) scores were generally lower than 11 other cancers.Conclusion: HRQoL impairment is grave in AML. Efforts are needed to improve HRQoL in affected patients.